(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
Abstract: Tarabuls (Tripoli) today is Tarabuls al-Gharb (Tripoli of the West) in the modern period, and it is Tarabuls in the Hafsi era and Atrabuls in the Umayyad era, and it is Atrabuls and Trabuls in the Fatimid and Zirid era. The toponym has known a journey in form, exactness, and spelling. Coins, Arabic sources, and official documents have proven this journey and this development in controlling and approving the name. And while the general public did not accept throughout the middle period mainly the authority’s decision to set the name for the western city to distinguish it from the eastern city (Tarabuls al-Sham), then in the modern period they no longer had a choice, as the Ottoman authority was more disciplined and applied the law, despite the existence of some few indications of the desire to delve into this issue again